EVALUATION RATINGS OF ENGINEERING UNIVERSITY ACTIVITIES - Nadezhda G. Yaruchkina; Vadim G. Tronin (Moscow Polytechnic University, 2016)
This article describes the formation of Webometrics rating, analyzes the strongand weak points of the methodology on the example UlSTU site. Also on the basis of UlSTU experience the paper suggests the ways to strengthen the position of Russian universities in this rating. The article analyzes the opportunities and challenges to increase the publication activity in journals included into the international databases such as Web of Science and Scopus for regional higher education institutions. The authors proposed to take into account factors affecting the employment of graduates, university participation in international projects aimed at improving the quality of education. It is advisable to consider the amount of intellectual property in the main results of the work of an engineering university in addition to journal publications.